ASSESSMENT OF GENETIC DIVERSITY IN COWPEA [VIGNA UNGUICULATA (L.) WALP.] GERMPLASM - H. K. MEENA; K. RAM KRISHNA; BHURI SINGH; TAPENDER KARELA (The Bioscan, 2015)
In the present study, seventy two genotypes of cowpea were evaluated for assessing genetic diversity for ten different quantitative characters for exploitation in a breeding programme aimed at improving yield potential of cowpea by using Mahalanobis D 2 statistics. The intra cluster D 2 value ranged from 0.00 to 43.96 while Inter cluster D 2 value ranged from 30.9 to 375.97 indicated that the selected genotypes were highly divergent. The maximum intra cluster distance was recorded for cluster IV (43.96) while cluster III and IX (0.00) showed no intra-cluster distance values revealed homogenous nature of the genotype within the cluster. The genetically more divergent genotypes present in cluster V and VIII as indicated by inter cluster distance value (375.97). Inter cluster D 2 value and mean cluster values for characters indicated that hybridization of clusters VIII with clusters V genotypes would result in marked heterosis and produce better segregants with improved yield. Among the characters studied, seed yield per plant (38.81%) contributed highest towards genetic divergence followed by 100-seed weight (29.07%). Selecting parents of these clusters probably provide promising recombinants and better segregants for future breeding strategy.